Energy Demand Analysis for Office Building Using Simulation Model and Statistical Method - Shakouri, Mahdi; Ghadamian, Hossein (Distributed Generation & Alternative Energy Journal, 2022)
This research is focused on the development of a reliable energy demand model for a case study using a comprehensive dual approach including: (1) engineering load calculation and simulation model via software and (2) statistical analysis. The simulated model is capable to cover the analysis of the cooling and thermal loads for a studied building. Concerning the building operation perspective, the statistical models were provided using the real measured data and multivariable regression analysis. For evaluating the performance of the developed statistical models, the authors have calibrated the models with the real measured data and then the impact of relevant variables has been evaluated through statistical tests and sensitivity analysis. According to the results of this study, the rated power for the cooling system and the capacity of the thermal system are 75.8 (kW) and 147.7 (kW), respectively. Based on the results of the statistical models, the measured and modelled data have been correlated with a strong coefficient of determination. The accuracy of models has been examined by calculating the statistical error indices with a suitable finding. Thus, the proposed models can be considered as an accurate findings for the energy performance analysis and demand forecasting objectives.